Femtosecond Stimulated Raman Spectroscopy. Issue 9 (18th March 2016) - Dietze, Daniel R.; Mathies, Richard A.
Abstract: Femtosecond stimulated Raman spectroscopy (FSRS) is an ultrafast nonlinear optical technique that provides vibrational structural information with high temporal (sub‐50 fs) precision and high spectral (10 cm −1 ) resolution. Since the first full demonstration of its capabilities ≈15 years ago, FSRS has evolved into a mature technique, giving deep insights into chemical and biochemical reaction dynamics that would be inaccessible with any other technique. It is now being routinely applied to virtually all possible photochemical reactions and systems spanning from single molecules in solution to thin films, bulk crystals and macromolecular proteins. This review starts with an historic overview and discusses the theoretical and experimental concepts behind this technology. Emphasis is put on the current state‐of‐the‐art experimental realization and several variations of FSRS that have been developed. The unique capabilities of FSRS are illustrated through a comprehensive presentation of experiments to date followed by prospects. Abstract : Structural dynamics is function : This review focuses on recent developments in femtosecond stimulated Raman spectroscopy, a technology that enables tracking vibrational structural changes of reacting molecules with unprecedented temporal precision and spectral resolution while being technologically simple enough to be widely accessible and applicable. The emphasis is on state‐of‐the‐art experimental realization as well as applications that provide new understandings of chemical and biochemical reactivity.